(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article explores the theoretical foundations for developing students’ scriptwriting skills through in-class instruction. It provides an analytical review of both local and international experiences and studies, leading to relevant conclusions. The article also identifies students’ knowledge and competencies in scriptwriting acquired through classroom activities.